Memperkuat Ekonomi Lokal dengan Bahasa Indonesia sebagai Media Penghubung dalam Transaksi Ekonomi Kecamatan Pulau-Pulau Aru - Sumarah Suryaningrum (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This research is motivated by the problem of communication in economic transactions in the Aru Islands District, which is recruited by a multi-ethnic community with a variety of regional languages. Although Indonesian has great potential as a national communication tool, its use in local economic activities is still limited, thus hampering the smooth interaction between traders and buyers. This communication inefficiency has an impact on the negotiation process and local economic competitiveness. This study aims to instill the role of Indonesian in facilitating economic transactions, identify barriers to use, and develop strategies to improve Indonesian language skills in the community. The approach used is descriptive qualitative with a phenomenological method. Data were collected through observation, in-depth interviews, and document studies, with informants selected using purposive sampling techniques to obtain data relevant to the local economic context. Expected results include an understanding of the contribution of Indonesian in increasing the effectiveness of transactions, revealing communication challenges, and strategies for improving contextual and applicable language literacy. These findings can provide practical contributions to local governments, educational institutions, and business actors in developing language training programs that support economic activities. From a theoretical perspective, this research enriches the study of the relationship between language and economic development, especially in multilingual areas such as the Aru Islands.